Development of High Performance Liquid Chromatographic Determination of Ambroxol, Roxithromycin and Serratiopeptidase in Combined Tablet Dosage Forms - G. Sailaja; P. R. K. Veni; B. Hari Babu (New Innovations in Chemistry and Biochemistry Vol. 3, 2021)
A simple, sensitive and accurate RP-HPLC method for the simultaneous quantification of ambroxol, roxithromycin and serratiopeptidase in bulk and combined tablet dosage form was developed and validated. Ambroxol, roxithromycin and serratiopeptidase were separated and estimated using Waters HPLC system and YMC Pack pro C18 (250 × 4.6 mm, 5 \(μ\)m particle size) column. The mobile phase consisted of 0.1% orthophosphoric acid and acetonitrile (60:40 v/v). The calibration curves were linear over concentration range of 12-36 \(μ\)g/mL, 60-180 \(μ\)g/mL and 6-18 \(μ\)g/mL with limits of detection of 0.040 \(μ\)g/mL, 1.176 \(μ\)g/mL and 0.127 \(μ\)g/mL for ambroxol, roxithromycin and serratiopeptidase, respectively. For the studied drugs, recovery varied in range of 99.57% - 100.24% with relative standard deviation ranging from 0.12% to 0.36%. The developed method was validated as per the ICH guidelines. The proposed RP-HPLC method could be used for the analysis of ambroxol, roxithromycin and serratiopeptidase simultaneously in combined tablet dosage forms.